Multisensory control of ingestive movements and the myth of food addiction in obesity. (13th December 2017) - Booth, David A.
Abstract: Some individuals have a neurogenetic vulnerability to developing strong facilitation of ingestive movements by learned configurations of biosocial stimuli. Condemning food as addictive is mere polemic, ignoring the contextualised sensory control of the mastication of each mouthful. To beat obesity, the least fattening of widely recognised eating patterns needs to be measured and supported.